2021
DOI: 10.3390/electronics10101211
|View full text |Cite
|
Sign up to set email alerts
|

Mitigating Children’s Pain and Anxiety during Blood Draw Using Social Robots

Abstract: Young pediatric patients who undergo venipuncture or capillary blood sampling often experience high levels of pain and anxiety. This often results in distressed young patients and their parents, increased treatment times, and a higher workload for healthcare professionals. Social robots are a new and promising tool to mitigate children’s pain and anxiety. This study aims to purposefully design and test a social robot for mitigating stress and anxiety during blood draw of children. We first programmed a social … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 49 publications
1
10
0
4
Order By: Relevance
“…Our findings are in line with previous studies which found that human-robot social interaction is effective in diminishing clinical pain. This effect was found in studies where the HRI was without any physical contact with the robot (Beran et al, 2013;Yasemin et al, 2016;Ruocco et al, 2019;Trost et al, 2020;Smakman et al, 2021) as well as in studies where the HRI involved touch (Such as hugging the robot and/or stroking it) (Tanaka et al, 2012;Eskander et al, 2013;Okita, 2013;Pu et al, 2019). In our previous experiment (Geva et al, 2020) we demonstrated that touching a social robot is more effective for pain reduction than social interaction with the robot that does not include physical contact.…”
Section: The Effect Of the Interaction With Paro On Pain Perceptionmentioning
confidence: 59%
See 1 more Smart Citation
“…Our findings are in line with previous studies which found that human-robot social interaction is effective in diminishing clinical pain. This effect was found in studies where the HRI was without any physical contact with the robot (Beran et al, 2013;Yasemin et al, 2016;Ruocco et al, 2019;Trost et al, 2020;Smakman et al, 2021) as well as in studies where the HRI involved touch (Such as hugging the robot and/or stroking it) (Tanaka et al, 2012;Eskander et al, 2013;Okita, 2013;Pu et al, 2019). In our previous experiment (Geva et al, 2020) we demonstrated that touching a social robot is more effective for pain reduction than social interaction with the robot that does not include physical contact.…”
Section: The Effect Of the Interaction With Paro On Pain Perceptionmentioning
confidence: 59%
“…For example, several studies demonstrated that HRI can increase positive emotions among healthy participants (Crossman et al, 2018;Geva et al, 2020;Hoffmann and Krämer, 2021). HRI was also found to reduce student stress during final exams (Edwards et al, 2020), reduce stress and anxiety among hospitalized children undergoing a medical procedure (Beran et al, 2013;Okita, 2013;Beran et al, 2015;Ruocco et al, 2019;Trost et al, 2019;Trost et al, 2020;Smakman et al, 2021) and among older adults living in senior healthcare settings (Góngora Alonso et al, 2019;Pu et al, 2019). It is important to note that all the mentioned studies did not report the role of plain touch compared to social touch in HRI.…”
Section: The Effect Of Social-touching Paro On Stressmentioning
confidence: 99%
“…Furthermore, our findings about the most valuable scenario and function for social robots are in line with the reported use of a social robot for distraction during needle insertion. [15,22] However, little value was seen in using social robots for educational purposes, even though many social robots are used for this purpose outside the field of pediatric oncology, for example in children with diabetes. [23,24] Furthermore, health care providers saw remarkably little value in using social robots with regard to sleep, even though 2 recent reviews reported sleep disruptions are frequent in children with cancer during treatment, [25,26] and no effective sleep interventions are known to exist.…”
Section: Discussionmentioning
confidence: 99%
“…Berdasarkan penelitian Smakman dan kawan-kawan, robot yang berbentuk manusia sangat menarik minat terutama anak-anak usia sekolah, pada penelitian ini, Smakman membagi kategori berdasarkan usia dengan pembagian kategori; Lower Class in Primary Education, Middle Class in Primary Education dan Hinger Class in Primary Education. Berdasarkan penelitian ini terdapat perbedaan nilai skala nyeri dan skala kecemasan yang lebih rendah pada kelompok Middle Class in Primary Education dibandingkan kelompok kontrol bahkan terhadap kelompok intervensi kategori Lower Class in Primary Education, dan Hinger Class in Primary Education (Smakman et al, 2021).…”
Section: Metodeunclassified
“…Sedangkan pada penelitian lainnya yaitu penelitian Smakman (Smakman et al, 2021), Trost (Trost, 2019), dan Farrier (Farrier et al, 2020 mendapatkan hasil penelitian skala nyeri dan skala kecemasan yang lebih rendah pada kelompok anak yang berinteraksi dengan robot dibandingkan dengan anak yang mendapatkan perawatan standar.…”
Section: Metodeunclassified